Untargeted metabolomics reveal the corrective effects of scorpion on epileptic mice - Lele Li; Shengyu Ge; Yang Wang; Heyun Zhu; Bo Feng (Scientific Reports)
Abstract Scorpion is a commonly used drug in traditional Chinese medicine for treating epilepsy, although the exact mechanisms are not yet fully understood. This study aimed to compare the treatment effects of Scorpion water extract (SWE) and Scorpion ethanol extract (SEE) on mice with pentetrazole-induced epilepsy and investigate the possible mechanisms through metabolomics methods. A pentetrazole-induced epileptic mice model was used to assess the corrective effects of SWE and SEE. Untargeted metabolomics, utilizing UPLC-Q-TOF/MS, was employed to analyze the metabolic profiles of mice and identify metabolic changes following scorpion treatment. The results revealed that only SWE showed therapeutic effects in epileptic mice. Metabolomics analysis demonstrated significant alterations in metabolic signatures between the pentetrazole-induced epileptic mice and SWE groups. By utilizing orthogonal partial least squares discrimination analysis, 44 and 108 potential biomarkers in mouse serum were identified in positive and negative ion modes, respectively. Differential metabolites related to epilepsy were then used to pinpoint relevant pathways in epileptic mice, such as linoleic acid metabolism, biosynthesis of unsaturated fatty acids, glycerophospholipid metabolism, and ether lipid metabolism. In conclusion, this study highlights the corrective effects of Scorpion on epileptic mice and provides insight into the underlying metabolic pathways involved in its efficacy.